Recent Research Progress in China on Haemonchus contortus - Wang, Chunqun; Li, Fangfang; Zhang, Zongze; Yang, Xin; Ahmad, Awais A.; Li, Xiangrui; Du, Aifang; Hu, Min (Frontiers in Microbiology, 2017)
Haemonchus contortus is one of the most important parasites of ruminants with worldwide distribution that can bring huge economic losses to the breeding industry of cattle, sheep, and goats. In recent 20 years, studies on H. contortus in China mainly focused on the epidemiology, population genetics, anthelmintic resistance, structural and functional studies of important genes regulating the development of this parasite, interaction between parasite molecules and host cells and vaccine development against haemonchosis, and achieved good progress. However, there is no systematic review about the studies by Chinese researchers on H. contortus in China. The purpose of this review is to bring together the findings from the studies on H. contortus in China in order to obtain the knowledge gained from the recent studies in China and provide foundation for identifying future research directions to establish novel diagnostic methods, discover new drug targets and vaccine candidates for use in preventing and controlling H. contortus in China.